Search for an anomalous excess of inclusive charged-current νe interactionsin the MicroBooNE experiment using Wire-Cell reconstruction - Abratenko, P; An, R; Antony, J; Duffy, KD; Van De Pontseele, W; Zhang, C (American Physical Society, 2022)
We report a search for an anomalous excess of inclusive charged-current (CC) νe interactions using the Wire-Cell event reconstruction package in the MicroBooNE experiment, which is motivated by the previous observation of a low-energy excess (LEE) of electromagnetic events from the MiniBooNE experiment. With a single liquid argon time projection chamber detector, the measurements of νµ CC interactions as well as π 0 interactions are used to constrain signal and background predictions of νe CC interactions. A data set collected from February 2016 to July 2018 corresponding to an exposure of 6.369 × 1020 protons on target from the Booster Neutrino Beam at FNAL is analyzed. With x representing an overall normalization factor and referred to as the LEE strength parameter, we select 56 fully contained νe CC candidates while expecting 69.6 ± 8.0 (stat.) ± 5.0 (sys.) and 103.8 ± 9.0 (stat.) ± 7.4 (sys.) candidates after constraints for the absence (eLEEx=0) of the median signal strength derived from the MiniBooNE observation and the presence (eLEEx=1) of that signal strength, respectively. Under a nested hypothesis test using both rate and shape information in all available channels, the best-fit x is determined to be 0 (eLEEx=0) with a 95.5% confidence level upper limit of x at 0.502. Under a simple-vs-simple hypotheses test, the eLEEx=1 hypothesis is rejected at 3.75σ, while the eLEEx=0 hypothesis is shown to be consistent with the observation at 0.45σ. In the context of the eLEE model, the estimated 68.3% confidence interval of the νe CC hypothesis to explain the LEE observed in the MiniBooNE experiment is disfavored at a significance level of more than 2.6σ (3.0σ) considering MiniBooNE’s full (statistical) uncertainties.